Модель безпеки інформаційної системи на базі технологій IoT - Мнушка, Оксана Василівна; Савченко, Володимир Миколайович (Національний технічний університет "Харківський політехнічний інститут", 2019)
Проаналізовано моделі безпеки комп’ютерних та інформаційних систем, компоненти яких мають доступ до мережних ресурсів. Запропоновано математичну модель для оцінки безпеки інформаційної системи на основі технологій Інтернету речей (Internet of things, IoT) у вигляді трибутивного метаграфу. На основі метрик Common Vulnerability Scoring System v. 3.0 проведено оцінку впливу кіберзагроз на компоненти веб-орієнтованої SCADA-системи.

The security models of computer and information systems, the components of which have access to network resources, are analyzed. A mathematical model is proposed for assessing the security of an information system based on the Internet of things (IoT) technologies in the form of an attribute metagraph. Based on the Common Vulnerability Scoring System v. 3.0, the impact of cyber threats on the components of a web-based SCADA-system was assessed.
Security model of an information system based on IoT technologies
Keywords: SCADA-системи; безпека комп'ютерних систем; математичні моделі; кіберзагрози; Common Vulnerability Scoring System; SCADA-system; security of computers; security of information systems; metagraph